Amnesia Associated with Bilateral Hippocampal and Bilateral Basal Ganglia Lesions in Anoxia with Stimulant Use - Haut, Marc W.; Hogg, Jeffery P.; Marshalek, Patrick J.; Suter, Blair C.; Miller, Liv E. (Frontiers in Neurology, 2017)
We report a case of a 55-year-old man with ischemic lesions of the bilateral hippocampus and bilateral basal ganglia following a myocardial infarction (MI) during an episode of multiple drug use with subsequent anoxia requiring resuscitation. He presented for a neuropsychological evaluation with an anterograde amnesia for both explicit and procedural memory. There are two main points to this case, the unique aspects of the bilateral multi-focal lesions and the functional, cognitive impact of those lesions. We hypothesize his rare focal, bilateral lesions of both the hippocampus and basal ganglia are a result of anoxia acting in synergy with his stimulant drug use (cocaine and/or MDMA). Second, his unique lesions produced an explicit and implicit/procedural anterograde amnesia.